2014
DOI: 10.1007/s10725-014-9953-5
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds from Alcaligenes faecalis JBCS1294 confer salt tolerance in Arabidopsis thaliana through the auxin and gibberellin pathways and differential modulation of gene expression in root and shoot tissues

Abstract: Volatile compounds from rhizobacteria are known to elicit and regulate plant growth and defense against various biotic and abiotic stresses. In the present study, we elucidated the biological role of volatiles from Alcaligenes faecalis strain JBCS1294 on the growth performance of Arabidopsis thaliana under salt stress. JBCS1294 volatiles promoted gains in fresh weight and shoot length of Arabidopsis Col-0 under salt stress by 61.5 and 45.8 %, respectively. Hexanedioic acid and butanoic acid were identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…For instance, Bhattacharyya et al . () identified several VOCs from A. faecalis including butyric acid, propionic acid and benzoic acid, and reported that those VOCs induced tolerance to salt stress in Arabidopsis thaliana by influencing the auxin and gibberellin pathways and upregulating the expression of key ion transporters (Bhattacharyya and Lee, ). In contrast to soluble compounds, volatile organic compounds can diffuse easily through air‐ and gas‐filled pores in the soil and likely play an important role in long‐distance microbial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bhattacharyya et al . () identified several VOCs from A. faecalis including butyric acid, propionic acid and benzoic acid, and reported that those VOCs induced tolerance to salt stress in Arabidopsis thaliana by influencing the auxin and gibberellin pathways and upregulating the expression of key ion transporters (Bhattacharyya and Lee, ). In contrast to soluble compounds, volatile organic compounds can diffuse easily through air‐ and gas‐filled pores in the soil and likely play an important role in long‐distance microbial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The VOCs released by Pseudomonadaceae significantly change the expressions of nutrition-storage proteins and γ-gamma-glutamyl hydrolase (Vaishnav et al, 2015). Moreover, a strain of Alcaligenes faecalis, JBCS1294 secretes extracellular adipic acid and butyric acid, which probably influences the synthetic pathway of auxin and gibberellins (Bhattacharyya et al, 2015).…”
Section: Endophytic Microorganisms Possibly Secrete Extracellular Commentioning
confidence: 99%
“…Alternatively, microbial VOCs can change root architecture by increasing root surface area, number of lateral roots and hairs, which in turn facilitate nutrient uptake (Ortiz-Castro et al, 2008;Splivallo et al, 2009;Ditengou et al, 2015;Garnica-Vergara et al, 2015;Casarrubia et al, 2016). (iii) Microbial VOCs can also affect plant hormone homeostasis (Bailly and Weisskopf, 2012;Bhattacharyya et al, 2014), which orchestrates vital plant growth and development (Davies, 2010). These changes in plant hormone homeostasis may be directly linked to plant phenotypic responses to microbial VOCs such as growth promotion through cell expansion (Zhang et al, 2007;Bitas et al, 2015) and cell division (Zhang et al, 2008;Sánchez-López et al, 2016) or changes in root architecture (Splivallo et al, 2009;Garnica-Vergara et al, 2015).…”
Section: From Plant Growth Inhibition To Growth Promotion and Faster mentioning
confidence: 99%
“…These changes in plant hormone homeostasis may be directly linked to plant phenotypic responses to microbial VOCs such as growth promotion through cell expansion (Zhang et al, 2007;Bitas et al, 2015) and cell division (Zhang et al, 2008;Sánchez-López et al, 2016) or changes in root architecture (Splivallo et al, 2009;Garnica-Vergara et al, 2015). Therefore, modulation of the hormone-signalling machinery and hormone transport by microbial VOCs can affect plant growth and development (Bailly and Weisskopf, 2012;Bhattacharyya et al, 2014;Tyagi et al, 2018).…”
Section: From Plant Growth Inhibition To Growth Promotion and Faster mentioning
confidence: 99%
See 1 more Smart Citation